Rational Design of Mixed Electronic‐Ionic Conducting Ti‐Doping Li7La3Zr2O12 for Lithium Dendrites Suppression. (13th May 2020) - Gao, Jian; Zhu, Jianxun; Li, Xiaolei; Li, Junpeng; Guo, Xiangxin; Li, Hong; Zhou, Weidong
Abstract: Garnet structured ceramic electrolyte Li7 La3 Zr2 O12 (LLZO) attracts much attention in solid‐state lithium batteries for its high ionic conductivity, wide electrochemical window, and lack of reducible element. However, the application of LLZO has been hindered by severe dendrite penetration. The theoretical investigations on the mechanisms of lithium dendrite evolution are carried out, aiming at quantifying the promotion effects of overpotential and the limitation counterpart of bulk modulus. Since dendrites preferentially propagate along connected defects, while intrinsic defects are difficult to be compeletely eliminated, manipulation of overpotential should be a more feasible way for dendrites suppression. The mixed electronic‐ionic conducting interphase, which in situ forms by introducing a Ti‐doping Li56 La24 Zr15 TiO96 (T‐LLZO) interlayer between Li and LLZO, is suggested based on the proposed mechanisms, which effectively facilitates to alleviate the overpotential thus suppress the lithium dendrites theoretically. This strategy is verified experimentally by obviously improved stability of Li/Li symmetric cell using T‐LLZO ceramic pellet electrolyte. Abstract : To better understand lithium dendrites formation in garnet‐structured Li7 La3 Zr2 O12 (LLZO), one of the most promising solid electrolyte owing to the high ionic conductivity and wide electrochemical window, the dendrite evolution process is simulated theoretically, and a strategy for Ti‐doping mixed electronic‐ionic interphase is proposed to alleviate overpotential and suppress lithium dendrites, which is verified experimentally to suppress the dendrites across Li/LLZO.